Pemanfaatan Tumbuhan Liar Sebagai Obat Meruyan Oleh Bapak Saukani Di Desa Namang - Aulia, Bela; Lihin, Giva; Assariy , Faiz Mush’ab; Priyansah, Sujadi (Lembaga Dongan Dosen, 2024)
Abstract− Obat Meruyan is a traditional herbal medicine whose recipe has been passed down from generation to generation and is now formulated by Mr. Saukani. Meruyan Medicine comes from Namang Village, Central Bangka Regency, Bangka Belitung Islands Province. Currently, Meruyan medicine is starting to be abandoned and replaced with ready-to-eat medicines sold in pharmacies and stores. For this reason, this research was conducted to educate and find out that the content of traditional medicine is safe for long-term consumption without causing side effects. In addition, traditional medicine is also effective in curing various diseases. Meruyan medicine has the main property of warding off various diseases that arise after childbirth, such as bloating, chills and constipation. Other properties include increasing stamina, improving blood flow, digestion, treating ulcers, fever, stomach acid, lowering blood sugar, hypertension and cholesterol. The method used in this research is descriptive qualitative. Data were obtained from interviews with medicine heirs and consumers. The results showed that 23 plant species and 18 families were used. The most widely used plant part in the concoction of Meruyan Medicine is the root. Meruyan medicine is consumed by boiling and drinking the water.